PENGARUH KOMUNIKASI DAN ETOS KERJA TERHADAP KINERJA TENAGA PEMASAR PADA PT PRUDENTIAL LIFE ASSURANCE PRESTASI AGENCY PS-1 PEMATANGSIANTAR - Sijabat, Ista Marsara; Lie, Darwin; Butarbutar, Marisi; Wijaya, Andy (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The formulation of this research problem is how the influence of communication and work ethic on the performance of marketers in PT Prudential Life Assurance Achievement Agency PS-1 Pematang Siantar. The research method used in this paper is literature research and field research. The population is 70 people marketers and the sample in this study as many as 70 people. The data used are data by qualitative and qualitative data, and data collection techniques by questionnaire, interview and documentation. Then the technique of data analysis using qualitative descriptive method and quantitative descriptive method. The result of analysis from multiple linear regression is Å¶ = 8,824 + 0,328X1 + 0,389X2, meaning that communication and work ethic have positive effect to marketer performance. The strength of the relationship between the three variables is very strong, ie r = 0.680. From the coefficient of determination can be explained the high performance of market power 46.3%, and the remaining 53.7% explained by other factors that are not discussed in this study. From the results of processing and calculation of the questionnaire, the authors get the conclusion that communication and work ethic at PT Prudential Life Assurance Agency PS-1 have a positive and significant impact on customer satisfaction. This is proven by hypothesis testing simultaneously, where the test result fhitung (28,828)> ftabel (3,13) with significance level 0,000 <alpha 0,05. Keywords: Communication, Work Ethic, Performance of Marketers